The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1936
DOI: 10.1152/ajplegacy.1936.116.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid in Rest and Work at High Altitude

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

1938
1938
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(38 citation statements)
references
References 0 publications
4
34
0
Order By: Relevance
“…In fact, some authors (Bender et al, 1989;Brooks et al, 1992Brooks et al, , 1998 have demonstrated that the low blood lactate concentration primarily depends on a reduced net lactate release from muscle fibres. The decrease in lactate accumulation could also be explained by the reduced alkalic reserves at high altitude (Edwards, 1936;Cerretelli, 1967;West, 1986). Although Kayser et al (1993) did not observe an increase in the peak of blood lactate concentration after ingestion of bicarbonate, it must be considered that bicarbonate is effective in muscle pH regulation only when it really enters the muscle cell and, after its conversion to CO 2, leaves the cell in the form of dissolved CO2.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some authors (Bender et al, 1989;Brooks et al, 1992Brooks et al, , 1998 have demonstrated that the low blood lactate concentration primarily depends on a reduced net lactate release from muscle fibres. The decrease in lactate accumulation could also be explained by the reduced alkalic reserves at high altitude (Edwards, 1936;Cerretelli, 1967;West, 1986). Although Kayser et al (1993) did not observe an increase in the peak of blood lactate concentration after ingestion of bicarbonate, it must be considered that bicarbonate is effective in muscle pH regulation only when it really enters the muscle cell and, after its conversion to CO 2, leaves the cell in the form of dissolved CO2.…”
Section: Discussionmentioning
confidence: 99%
“…Not to be inattentive or otherwise neglectful of then contemporary science, as described by Reeves [ 9 ], pioneer workers such as Dill et al [ 10 ] and Edwards et al [ 11 ] took an early interest in the lactate response at altitude. In the 1929 expeditions to Leadville, CO [ 10 ] and the Andes in Chile [ 11 ] observed in unacclimatized sojourners that during rest and exercise, blood lactate concentrations were evaluated at altitude above those seen at sea level.…”
Section: Early Studies At Altitudementioning
confidence: 99%
“…In the 1929 expeditions to Leadville, CO [ 10 ] and the Andes in Chile [ 11 ] observed in unacclimatized sojourners that during rest and exercise, blood lactate concentrations were evaluated at altitude above those seen at sea level. The conclusion at that time regarding the elevation in blood lactate was classic and based on the Pasteur Effect , glycolytic fl ux was increased because oxidative metabolism was limited.…”
Section: Early Studies At Altitudementioning
confidence: 99%
“…I hope always to be faithful in prayer and trust our Lord, Amen." Subsequent Observations.-The patient was discharged from the hospital on Sept. 16,1936. She looked around Boston for a job and then went home.…”
Section: Report Of Casementioning
confidence: 99%
“…At high altitude diminished concentration of bicarbonate is not associated with increased concentration of lactate. 16 In experi¬ ments on hyperventilation at sea level, however, the increase in concen¬ tration of lactate may be 2 or 3 milliequivalents per liter.17 This may account for the greater portion of the undetermined acid.…”
Section: Commentmentioning
confidence: 99%